2020
DOI: 10.1093/jscr/rjaa493
|View full text |Cite
|
Sign up to set email alerts
|

Struma ovarii: two case reports of a rare teratoma of the ovary

Abstract: Struma ovarii is an extremely rare type of ovarian teratoma distinguished by the unusual presence of thyroid tissue. It is usually a benign condition; however, malignant transformation is sometimes detected. The diagnosis relies on histopathological examination and is infrequently made on routine investigations. We report two cases of struma ovarii: one benign and the other malignant. The first case involved a 27-year-old woman who underwent a right ovarian cystectomy for an incidental ultrasonographic finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…In most cases, MSO is discovered incidentally during routine ultrasonography, due to the lack of specificity regarding clinical or imaging criteria [ 6 , 9 , 10 ]. Retrospective studies have shown that as much as 40% of patients are asymptomatic, the diagnosis being often delayed [ 11 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, MSO is discovered incidentally during routine ultrasonography, due to the lack of specificity regarding clinical or imaging criteria [ 6 , 9 , 10 ]. Retrospective studies have shown that as much as 40% of patients are asymptomatic, the diagnosis being often delayed [ 11 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Struma ovarii (SO) is a rare monodermal variant of ovarian teratoma that contains predominantly thyroid tissue (> 50%), accounting for 0.5-1% of all ovarian tumors and 2-5% of ovarian teratomas [1][2][3][4]. It may present any form of thyroid pathology, and in most cases is a benign condition, but approximately 5-10% of these tumors become malignant (MSO), with papillary and follicular carcinoma most common [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 5-8% of cases are associated with clinical hyperthyroidism. These tumors are often diagnosed incidentally after surgery (9). The thyroid gland of these patients is not enlarged, and radioiodine uptake is low or absent in their thyroid gland; however, it often accumulates in their pelvis (10,13).…”
Section: Discussionmentioning
confidence: 99%
“…The initial footprint of the tumor is mostly based on incidental imaging, but definitive diagnosis is possible based on pathological studies. Surgical resection of the tumor followed by adjuvant radioiodine therapy has been accepted as the definitive therapeutic approach leading prevention of disease metastasis or recurrence (5). Herein, we described a case of struma ovarii that was successfully diagnosed and managed.…”
Section: Introductionmentioning
confidence: 99%